2021
DOI: 10.1007/s11427-021-2024-0
|View full text |Cite
|
Sign up to set email alerts
|

Rice functional genomics: decades’ efforts and roads ahead

Abstract: Rice (Oryza sativa L.) is one of the most important crops in the world. Since the completion of rice reference genome sequences, tremendous progress has been achieved in understanding the molecular mechanisms on various rice traits and dissecting the underlying regulatory networks. In this review, we summarize the research progress of rice biology over past decades, including omics, genome-wide association study, phytohormone action, nutrient use, biotic and abiotic responses, photoperiodic flowering, and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 660 publications
(717 reference statements)
0
98
0
Order By: Relevance
“…With the development of multi-omics technologies and related data processing pipelines ( Feng et al, 2021 ; Iqbal et al, 2021 ), the hierarchical regulation network of the circadian clock will be gradually parsed and applied to improve rice traits. Recently, the representative role of OsPRR37 in the control of photoperiodic flowering was systematically reviewed ( Chen et al, 2021 ; Zhou et al, 2021c ). However, the underlying mechanism of how OsPRR37 regulates its output genes to affect multiple agronomic traits remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of multi-omics technologies and related data processing pipelines ( Feng et al, 2021 ; Iqbal et al, 2021 ), the hierarchical regulation network of the circadian clock will be gradually parsed and applied to improve rice traits. Recently, the representative role of OsPRR37 in the control of photoperiodic flowering was systematically reviewed ( Chen et al, 2021 ; Zhou et al, 2021c ). However, the underlying mechanism of how OsPRR37 regulates its output genes to affect multiple agronomic traits remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further revealed a distinct role of OsPRR37 in promoting flowering in the japonica variety Zhonghua 11 under natural long-day conditions ( Hu et al, 2021 ). Although several output genes involved in the photoperiodic flowering pathway are used to explain the trait variations ( Chen et al, 2021 ; Zhou et al, 2021c ), the underlying mechanism of how OsPRR37 regulates its output genes and multiple traits remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Na + , K + content, and Na + /K + ratio are important indexes for measuring rice ST [ 37 ]. High-affinity K + transporters (HKT) can effectively stabilize Na + at the cell level [ 38 ]. OsHKT1;5 excretes Na + from the roots’ xylem parenchyma cells (XPC) [ 39 ].…”
Section: Phenology Physiological and Biochemical Indicators Of Drough...mentioning
confidence: 99%
“…Increased ABA content induces stomatal closure and reduces water loss in guard cells, which has a significant impact on osmotic potential reduction [ 45 ]. The ABA signaling pathway, acting as a pivotal process in biotic and abiotic stress responses, plays an important role in drought and salt responses [ 38 , 46 ]. The main components in the core ABA signaling transduction pathway include ABA receptors PYR/PYL/RCARs, SnRK2s and ABA co-receptor branch type A 2C protein phosphatase (PP2Cs) [ 41 , 47 ].…”
Section: Phenology Physiological and Biochemical Indicators Of Drough...mentioning
confidence: 99%
See 1 more Smart Citation